2019
DOI: 10.1136/fmch-2018-000063
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of new family physicians finding jobs with obstetrical care in the USA

Abstract: ObjectiveThis study aimed to explore how new family medicine graduates who want to include obstetrics in their scope of practice identify and select jobs and to understand how employment influences scope of practice in family medicine, particularly the ability to provide maternity care and deliver babies.DesignMixed-methods study including a survey and qualitative interviews conducted in 2017.SettingWe electronically surveyed US family physicians and followed up with a purposeful subsample of these physicians … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 24 publications
0
22
0
Order By: Relevance
“…18 While only 8% of current family physicians include OB in their practice, nearly 22% of recent graduates intend to include OB in their practice. 19 While conducting a qualitative study of recent family medicine graduates to better understand the motivating factors and barriers faced by FPs who want to include obstetric deliveries in their practice, 20,21 we found that almost all participants discussed the concept of burnout related to practicing OB. We aimed to explain how and why practicing OB might be associated with lower levels of burnout 13 by examining the ways in which FPs discussed the relationship between practicing OB and burnout.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…18 While only 8% of current family physicians include OB in their practice, nearly 22% of recent graduates intend to include OB in their practice. 19 While conducting a qualitative study of recent family medicine graduates to better understand the motivating factors and barriers faced by FPs who want to include obstetric deliveries in their practice, 20,21 we found that almost all participants discussed the concept of burnout related to practicing OB. We aimed to explain how and why practicing OB might be associated with lower levels of burnout 13 by examining the ways in which FPs discussed the relationship between practicing OB and burnout.…”
Section: Resultsmentioning
confidence: 95%
“…As reported in detail elsewhere, 20,21 in 2017, we conducted semistructured telephone interviews with 56 recent family medicine graduates to understand intention to include OB in their practice. We used data from the American Board of Family Medicine (ABFM) to identify and recruit all FPs who graduated from residency between 2014 and 2016 and who, upon registering for their Board certification exam, indicated that they planned to include obstetric deliveries in their practice.…”
Section: Methodsmentioning
confidence: 99%
“…Many of today's family medicine residencies exist in compromised settings where the prevailing scope of practice is much narrower than that desired by residency applicants. 3,4 This needs to change. The health of America's small towns, underserved communities, and rural hospitals depends on our choices now.…”
mentioning
confidence: 99%
“…2,3 A growing number of recent family medicine graduates prefer to work in large practices for a better work-life balance and to avoid the administrative burdens and other responsibilities associated with owning a practice. 3,4 It is unclear if these advantages lead to fewer family physicians (FPs) in small and solo practices.…”
mentioning
confidence: 99%